2002
DOI: 10.1063/1.1500778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a thin GaAs cap layer on structural and optical properties of InAs quantum dots

Abstract: In this letter we investigate the changes in the surface morphology and emission wavelength of InAs quantum dots (QDs) during initial GaAs encapsulation by atomic force microscopy and photoluminescence. The density (2.9×1010 cm−2) and height (7.9±0.4 nm) of the uncapped QDs decrease and saturate at 0.6×1010 cm−2 and 4 nm, respectively, after the deposition of 4 monolayers (MLs) of GaAs. A model for the evolution of surface morphology is proposed. Photoluminescence spectra of the surface dots show a wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 15 publications
6
41
2
2
Order By: Relevance
“…The blue shift can also been attributed to a reduction of the QD height as the cover layer thickness is increased. 6 Similar results have been observed for other systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 and InP/InGaP. 9 We should also consider the contribution of the intermixing at the interfaces, which results in a blue shift.…”
Section: A Structural Analysismentioning
confidence: 49%
See 1 more Smart Citation
“…The blue shift can also been attributed to a reduction of the QD height as the cover layer thickness is increased. 6 Similar results have been observed for other systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 and InP/InGaP. 9 We should also consider the contribution of the intermixing at the interfaces, which results in a blue shift.…”
Section: A Structural Analysismentioning
confidence: 49%
“…On the other hand, the optical analysis of any SAQDs is usually performed using embedded dots, since the surface states act as efficient non-radiative channels for uncapped dots. Previous studies using uncapped SAQDs have indeed observed weaker photoluminescence ͑PL͒ as compared to capped dots on systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 Ge/Si, 8 and InP/InGaP. 9 In contrast, uncapped InP/GaAs SAQDs present an efficient PL emission that allows us to obtain structural and optical properties from the same sample, which is actually a very important advantage when investigating SAQD properties.…”
Section: Introductionmentioning
confidence: 99%
“…Two factors are believed to have contributed to the dots size fluctuations. Firstly, earlier studies have indeed shown that InAs/GaAs dots undergo morphological changes during the initial stage of capping process, due to thermally activated surface indium segregation [23,24]. It was also found that top of the dots would likely remain exposed when they are overgrown by a very thin GaAs layer [23].…”
Section: Resultsmentioning
confidence: 97%
“…Firstly, earlier studies have indeed shown that InAs/GaAs dots undergo morphological changes during the initial stage of capping process, due to thermally activated surface indium segregation [23,24]. It was also found that top of the dots would likely remain exposed when they are overgrown by a very thin GaAs layer [23]. Secondly, the GaAs cap layers in our samples were deposited in two steps, separated by a growth interruption (of $8 min) to ramp T sub from 500 up to 580 8C.…”
Section: Resultsmentioning
confidence: 99%
“…the growth was terminated after completion of the QD layer with no subsequent overgrowth with InAs. This may not truly reflect the actual QD shape and density in the actual detector structures as the capping material is known to strongly influence the QD formation [14]. Nonetheless, under these conditions it is noted that a GaAs dot density comparable to reported molecular beam epitaxy (MBE) results [15,16] can be achieved.…”
Section: Methodsmentioning
confidence: 90%